Lignin and stem flexibility in eucalyptus seedlings subjected to hardening - Lima, Paulo Ricardo (2020)
The objective of this work was to verify if hardening by stem bending and foliar spray of jasmonic acid (JA) induced lignification and if it altered the post-planting development. The experiment was initially conducted in a shade house following a completely randomized design with treatments as (T1) control; (T2) 2.0 μmol L-1 of JA; (T3) 4.0 μmol L-1 of JA; (T4) 6.0 μmol L-1 of JA; (T5) 8.0 μmol L-1 of JA; (T6) 20 stem bending; (T7) 40 stem bending and five replicates. At the end of the imposed treatments, we calculated the increments in height, stem diameter, number of leaves, root and shoot dry biomasses, as well as the lignin content of shoots and roots and the stem stiffness. Afterwards, seedlings were planted following a randomized block design with three seedlings per replicate. At 90 and 150 days after planting, we quantified increments in height and stem diameter. Treatments T5 and T6 showed higher bending strength (0.28885 and 0.3005 N cm-1, respectively). Seedlings submitted to doses above 6.0 μmol L-1 of JA (T5) and imposition of stem bending (T6 and T7) resulted in a higher stem lignin content. The smaller doses of JA (T2, T3 and T4) and 20 stem bending (T6) resulted in seedlings with a relative increase in diameter. The interpretation of path analysis showed weak multicollinearity, that is, the variables under study are not highly correlated and there was a greater direct correlation between the lignin content of the stem with the mean increase in height and diameter of the seedlings after planting.